Unlocking the potential of smallholder dairy farm: Evidence from the central highland of Ethiopia - Feyissa, Abraham Abera; Senbeta, Feyera; Tolera, Adugna; Guta, Dawit Diriba (Elsevier, 2023)
Sustainable livestock farming practices have the potential to improve productivity and high income, reduce greenhouse gases, and improve household food security. Despite previous efforts to disseminate these technologies, the rate of adoption has remained very low in Ethiopia. In this study, we investigate the determinants of adoption and the impact of improved dairy farming practices (IDFP), which include improved breed, improved feed, and improved feeding conditions, on household food security in the central highland of Ethiopia.